Splicing factor gene mutations in the myelodysplastic syndromes: impact on disease phenotype and therapeutic applications. - Pellagatti, A; Boultwood, J (Elsevier, 2016)
Splicing factor gene mutations are the most frequent mutations found in patients with the myeloid malignancy myelodysplastic syndrome (MDS), suggesting that spliceosomal dysfunction plays a major role in disease pathogenesis. The aberrantly spliced target genes and deregulated cellular pathways associated with the commonly mutated splicing factor genes in MDS (SF3B1, SRSF2 and U2AF1) are being identified, illuminating the molecular mechanisms underlying MDS. Emerging data from mouse modelling studies indicate that the presence of splicing factor gene mutations can lead to bone marrow hematopoietic stem/myeloid progenitor cell expansion, impaired hematopoiesis and dysplastic differentiation that are hallmarks of MDS. Importantly, recent evidence suggests that spliceosome inhibitors and splicing modulators may have therapeutic value in the treatment of splicing factor mutant myeloid malignancies.